1984
DOI: 10.1104/pp.75.4.1099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammonium on Nitrate Utilization by Roots of Dwarf Bean

Abstract: The effect of exogenous NH4' on NO3-uptake and in vivo NO3-reductase activity (NRA) in roots of Phascolus vulgaris L. cv Witte Krombek was studied before, during, and after the apparent induction of root NRA and NO3-uptake. Pretreatment with NH41 (0.15-50 milli-molar) affected neither the time pattern nor the steady state rate of N03-uptake. When NH4' was given at the start of NO3-nutrition, the time pattern of NO3-uptake was the same as in plants receiving no NH,4. After 6 hours, however, the NO3-uptake rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 23 publications
(20 reference statements)
3
52
3
Order By: Relevance
“…These results differ with the findings of previous investigations conceming the effect of NH4+ pretreatments on the apparent indiiction of NO3-uptake (Jackson et al, 1972;Tdmpkins et al, 1978;Breteler and Siegerist, 1984).…”
Section: The Effect Of Ammoniumcontrasting
confidence: 57%
See 1 more Smart Citation
“…These results differ with the findings of previous investigations conceming the effect of NH4+ pretreatments on the apparent indiiction of NO3-uptake (Jackson et al, 1972;Tdmpkins et al, 1978;Breteler and Siegerist, 1984).…”
Section: The Effect Of Ammoniumcontrasting
confidence: 57%
“…Previous investigations, in which pretreatments with NH4+ were administered to test the effect on the induction of NO3-uptake, have yielded conflicting results (Breteler and Jackson et al, 1972;Tompkins et al, 1978;Siegerist, 1984;Bloom and Sukrapanna, 1990). The results of a majority of experiments suggest that NH4+ pretreatments have a slight inhibitory effect on the induction of NO3-uptake or no effect at all.…”
Section: The Effect Of Ammoniummentioning
confidence: 99%
“…13,14) The shifting pattern of NH4.m+/NO3.m-values in NG on media 4 to 6 was also supposed to be similar to that on MS medium.…”
Section: Resultsmentioning
confidence: 99%
“…Jackson et al (1980) reported that the nitrate uptake was regulated by the carbohydrate supply status in roots of maize seedlings. It has been reported that the nitrate uptake is inhibited by nitrate accumulation in root cells (King et al 1993), several products of ammonia assimilation (Breteler and Siegerist 1984), and amino acids such as arginine, alanine, asparagine, glutamine (Muller and Touraine 1992). Imsande and Touraine (1994) assumed that the nitrate uptake is controlled by the rate of organic acid translocation and amino acid concentration in the phloem.…”
Section: Discussionmentioning
confidence: 99%